Physicochemical characterization of siliceous sands of Seme-Podji/Benin: An application for the synthesis of silica particles - Glitho, Houefa Annick Leslie; Osseni, Semiyou Ayele; Bonou, Sidoine Sourou; Plaisier, Jasper; Gigli, Lara; Sagbo, Etienne; Chouti, Waris Kewouyemi (European Journal of Chemistry, 2024)
In order to valorize locally available natural resources, the silica sand in the commune of Sèmè-Podji in Republic of Benin was characterized. The results obtained by particle size, chemical analysis, X-ray diffraction (XRD), and FT-IR analysis confirmed that these sands contain a high percentage of silicon dioxide, with a value approximately equal to 90 wt.%. Low Fe2O3 and Al2O3 content (<1 wt.%) and minor oxides such as K2O, Na2O, TiO2, and P2O5 (<0.6%) were also present. The size distributions of the particles show that the largest portion of the sand is found between 63 and 125 μm. This portion represents the one that contains the most silica. From this sand, silica particles were synthesized by the sol-gel method. The results obtained by X-ray diffraction (XRD), FT-IR analysis, and scanning electron microscopy (SEM) reveal the formation of pure amorphous silica.